2005
DOI: 10.1159/000086080
|View full text |Cite
|
Sign up to set email alerts
|

Use of Tissue Doppler to Assess Right Ventricle Function in Hemodialysis Patients

Abstract: Aims: Although there are plenty of data about the differences in left ventricular tissue Doppler (TD) velocities by preload reduction, only a few studies regarding right ventricular function are found in the literature. We investigated the effect of intravascular volume reduction on right ventricular function by ultrafiltration in dialysis patients. Methods: 27 end-stage renal failure patients who were hypervolemic and undergoing hemodialysis were included in the study. TD studies of the right ventricle were p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 34 publications
1
20
0
1
Order By: Relevance
“…MPI is one of the most accurate indices of ventricular performance since it includes parameters relative to both cardiac contraction and relaxation [19,20]. Moreover, MPI estimation based on tissue Doppler analysis is relatively independent from intravascular volume reduction after HD [23]. In our study, TDI indices of right ventricular systolic and diastolic function were significantly reduced in HD patients compared to PD patients and controls.…”
Section: Discussionmentioning
confidence: 54%
“…MPI is one of the most accurate indices of ventricular performance since it includes parameters relative to both cardiac contraction and relaxation [19,20]. Moreover, MPI estimation based on tissue Doppler analysis is relatively independent from intravascular volume reduction after HD [23]. In our study, TDI indices of right ventricular systolic and diastolic function were significantly reduced in HD patients compared to PD patients and controls.…”
Section: Discussionmentioning
confidence: 54%
“…Arinc et al showed that RV systolic and diastolic velocities detected by TDI were not or only minimally aff ected from preload reduction in hemodialysis patients [21]. Drighil et al showed that both systolic and diastolic TDI velocities of the RV are preload dependent [22].…”
Section: Discussionmentioning
confidence: 99%
“…LV contributes to right ventricular systolic pressure and outfl ow volume with a rate of 20 to 40% (Santamore and Dell'Italia 1998). Arinc et al (2005) reported that peak velocities of tricuspid lateral annulus were decreased following an effective hemodialysis parallel to a reduction in preload and pulmonary artery systolic pressure. Consequently, changes in tissue Doppler parameters of tricuspid lateral annulus refl ect improvement in myocardial diastolic function induced by HBO therapy.…”
Section: Discussionmentioning
confidence: 99%